دراسة واقع وآفاق الصيرفة الإسلامية في الجزائر في ظل الإصلاحات المصرفية 2018-2020 - شاني, محمد عبد الوهاب; حديدي, آدم (جامعة الوادي - University of Eloued, 2023)
نهدف هذه الدراسة إلى تبيان واقع وآفاق الصيرفة الإسلامية في الجزائر في ظل الإصلاحات المصرفية 2018-2020 وذلك في ظل التسرب النقدي الكبير والمحصي بحوالي 6000 مليار دينار جزائري ككتلة نقدية مكتنزة ومتداولة خارج القطاع الرسمي، وفي سبيل ذلك تم الاعتماد على المنهج الوصفي التحليلي من خلال عرض وتحليل أهم المؤشرات المالية للمؤسسات المصرفية الإسلامية في الجزائر، حيث تم التوصل إلى أن التوجه نحو الصيرفة الإسلامية هو الحل الأمثل للدفع بعجلة التنمية الاقتصادية والاجتماعية خاصة في ظل شح الموارد المالية، نظرا لقدرتها على استقطاب الأموال وتوجيهها للاستثمار، كما يعد نقلة نوعية لتطوير الصناعة المالية الإسلامية في الجزائر. ويفتح آفاق لتحقيق النمو الاقتصادي ظل رفض المجتمع الجزائري التعامل مع البنوك الربوية. This study aims to clarify the reality and the prospects of Algerian Islamic bankingin the light of banking reforms 2018-2020, and this is in view of the large cash discharge which is estimated at about 6999 billion Algerian dinars, as main part cash block and current outside the official sector, and for that The descriptive analytical approach was relied upon by presenting and analysing the most important financial indicators for Algerian Islamic banking institutions, Where it was concluded that the tendency towards Islamic banking is the perfect solution wheel of economic and social development, resources scarcity, Due to its ability to attract funds and direct them for investment.It’s also a qualitative leap for the development of the Algerian Islamic financial industry, andit opens up prospects for achieving economic growth in light of the Algerian society refusalto.
A Study of the Reality and Prospects for Developing Islamic Banking in Algeria, According to Banking Reforms 2018-2020.
مقال
Keywords: الصيرفة الإسلامية؛ البنوك الإسلامية؛ النوافذ المالية الإسلامية؛ الإصلاحات المصرفية.